2018
DOI: 10.15446/abc.v23n1.64962
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic response to low and high light of cacao growing without shade in an area of low evaporative demand

Abstract: Cacao (Theobroma cacao L.) breeding programmes in Ecuador have focused on obtaining high-yield clones with improved disease resistance. Cacao clones should also have photosynthetic characteristics which support increased productivity. Regarding the weather conditions at the coast of Ecuador, where most of the year there are overcasts and low air evaporative demand, there is the possibility to grow cacao without overhead shade. This study focused on the photosynthetic response at two different photosynthetic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
27

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 20 publications
(19 reference statements)
5
32
0
27
Order By: Relevance
“…The P N and g s values in adult trees of Chuao cocoa in the field were similar to those of seedlings in the greenhouse experiment, which is not surprising, since daily PPFD growth was similar between ML and F; similar values of P N and g s have been reported in trees of other cocoa Criollos and Trinitarios cultivars (De Almeida et al , Tezara et al ). The low values of P N and g s measured in plants subjected to different PPFD in the greenhouse and in the field are similar to those reported in other cocoa clones under different growth conditions (Joly and Hahn , Miyaji et al , Daymond et al , Araque et al , Almeida et al , Ávila‐Lovera et al ) and lower than those reported for coffee (Rodríguez‐López et al ) and Ecuadorian sun cocoa (Jaimez et al ). The absence of differences in P N and g s between the greenhouse and field plants contrasts with observations done in coffee, in which the source/sink imbalance imposed by root restriction due to pot size severely reduced P N (Ronchi et al ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The P N and g s values in adult trees of Chuao cocoa in the field were similar to those of seedlings in the greenhouse experiment, which is not surprising, since daily PPFD growth was similar between ML and F; similar values of P N and g s have been reported in trees of other cocoa Criollos and Trinitarios cultivars (De Almeida et al , Tezara et al ). The low values of P N and g s measured in plants subjected to different PPFD in the greenhouse and in the field are similar to those reported in other cocoa clones under different growth conditions (Joly and Hahn , Miyaji et al , Daymond et al , Araque et al , Almeida et al , Ávila‐Lovera et al ) and lower than those reported for coffee (Rodríguez‐López et al ) and Ecuadorian sun cocoa (Jaimez et al ). The absence of differences in P N and g s between the greenhouse and field plants contrasts with observations done in coffee, in which the source/sink imbalance imposed by root restriction due to pot size severely reduced P N (Ronchi et al ).…”
Section: Discussionsupporting
confidence: 85%
“…This was more marked in adult trees, in which P Nsat was on average half the value in seedlings. Higher P Nsat and LSP in HL plants after 3 months, ML and HL plants after 6 months and F plants indicate that Chuao cocoa adapts to sun conditions, as in the case of Ecuadorian cocoa (Jaimez et al ). Values of LSP, 250 μmol m −2 s −1 on average, were relatively low in the greenhouse and similar to the value for other cocoa cultivars (Joly and Hahn , Balasimha et al , Baligar et al , Almeida et al , Tezara et al ), even lower values (110 μmol m −2 s −1 ) have been found in adult trees under natural conditions in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The development of the DPI was based on data collected over four years (February 2011 to December 2015) from an experiment carried out by the Cacao and Coffee Programme of the National Institute of Agricultural Research (INIAP) at the Pichilingue Tropical Experimental Station in Mocache, Los Ríos province, Ecuador. In this experiment, 30 clones were planted in March 2008 using a randomized complete block design with two blocks (Jaimez et al , ). Each block consisted of 15 rows with 10 plants per row.…”
Section: Methodsmentioning
confidence: 99%
“…Annual fertilization was based on a nutritional requirement analysis obtained when the plantation field plots were initiated (Jaimez et al , ). Shape pruning and sanitary pruning started the second year to maintain tree structure and to remove brooms caused by M. perniciosa , respectively.…”
Section: Methodsmentioning
confidence: 99%